2021
DOI: 10.1177/00469580211029599
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Staff’s Adherence to Information Security Policy: A Quest for the Antecedents of Deterrence Variables

Abstract: Information security has come to the forefront as an organizational priority since information systems are considered as some of the most important assets for achieving competitive advantages. Despite huge capital expenditures devoted to information security, the occurrence of security breaches is still very much on the rise. More studies are thus required to inform organizations with a better insight on how to adequately promote information security. To address this issue, this study investigates important fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…The following factors appeared in two studies: Perceived certainty is derived from GDT, which can examine different acts or processes, such as detection [ 80 ] and punishment [ 73 ]. Two selected studies evaluated the impacts of peer influence and superior influence on different types of security behavior: protection intention [ 70 ] and non-compliance intention [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…The following factors appeared in two studies: Perceived certainty is derived from GDT, which can examine different acts or processes, such as detection [ 80 ] and punishment [ 73 ]. Two selected studies evaluated the impacts of peer influence and superior influence on different types of security behavior: protection intention [ 70 ] and non-compliance intention [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…The different perspectives of these theories and the facilitating conditions show the whole chain of the InfoSec behaviour adoption process. Thus, it helps organisations reduce information security breaches by changing employees' behaviour to match information security policies and rules [7,15,[17][18][19][20][21][22]. An assessment of theories utilised in related work revealed that the theories of TPB, PMT, and GDT are most often used [23]; [24].…”
Section: Theoretical Background and Conceptual Modelmentioning
confidence: 99%
“…GDT has been chiefly used in criminology to minimise deviant behaviour in people. In recent decades, it has been successfully and efficiently used for information technology as well as preventative information security [15], [19], [20], [27], [43]. In GDT, the deterrence model is built on three core constructs: certainty of sanctions, the severity of sanctions, and celerity of sanctions.…”
Section: Deterrence Factorsmentioning
confidence: 99%
See 2 more Smart Citations